Daylight performance analysis of a residential building in a tropical climate - Kalaimathy, Kamaraj; Shanthi Priya, Radhakrishnan; Rajagopal, Prashanthini; Pradeepa, Chandramouli; Senthil, Ramalingam (Energy nexus, 2023)
•The daylight performance of a ground floor of a two-storey residence is studied.•Design-Builder simulation is used to evaluate useful daylight illuminance.•Annual sunlight exposure and spatial daylight autonomy are analysed.•A window-to-wall ratio of 16% benefits the optimal daylighting performance.•The preferred visible light transmittance with a minimal glare is 0.62. The present study investigates the effects of visible light transmittance in glazing and window-to-wall ratios on the ground floor daylighting performance in a two-storey residential building in a warm-humid climate. The metrics used to optimize daylighting performance with minimal glare are useful daylight illuminance, annual sunlight exposure, and spatial daylight autonomy. The daylighting performance of a residential building is assessed by empirical method and Design-Builder simulation, focusing on overcast sky situations. The useful daylight illuminance is the primary metric for analysing the amount of daylight throughout the year. Annual sunlight exposure and spatial daylight autonomy complement useful daylight illuminance in evaluating the daylighting performance. A window-to-wall ratio of 16%, a visible light transmittance of 0.62, and a glare of 0.52 can meet the daylighting requirements and standards. A design change in the window position helps to obtain annual sunlight exposure within 10% while maintaining high daylighting performance. When installed in the upper position of the wall with a higher sill and lintel height, glazing with a window-to-wall ratio of 16% and a visible light transmittance of 0.62 functions well without creating glare. The significant findings benefit all stakeholders in improving daylighting strategies in tropical climates and satisfying building standards.